Degradasi Akta Otentik yang Tidak Dilakukan Penandatanganan Para Pihak Secara Bersama - Dian Dharmayanti; Rr Asfarina Izazi Razan; Nahdlotul Fadilah (Perspektif Hukum, 2019)
Notary is a general officer authorized to create an authentic deed of all actions, agreements, and statutes required by the laws and/or regulations required by the interested to be expressed in the deed Authentically, guaranteeing the certainty of the date of the deed, storing the deed, giving Grosee, copies and quotations of the deed, all of them throughout the making of the deed were not also assigned or excluded to the other officers stipulated by the law. Thus, it is described in article 1 number 1 of Law No. 2 of 2014 concerning the amendment to law Number 30 year 2004 concerning the Notary Regulation (Hereinafter called UUJN). A notary public is a noble, independent and high integrity position, so it is only natural to take all actions in their position seriously referring to the laws and regulations and the code of ethics. The law actions of the parties as described in the notarial deed is purely wishes of the parties and the notary is limited to providing law counseling related to the contents of the deed and the law actions of the parties, without imposing the will of the parties. party or in favor of one party. After the deed is made and then read out in front of the parties and witnesses, it must be signed when it is signed by all parties present and witnesses as well, it becomes one of the notary obligations stipulated in UUJN.